Effects of Hibiscus sabdariffa Linn. on insulin-like growth factor binding protein 3 (IGFBP-3) to prevent overtraining syndrome (Faculty of Medicine Universitas Indonesia, 2014)
Background: Excessive physical exercises (overtraining) can increase the production of reactive oxygen species (ROS). One of the indicators of overtraining syndrome is a decrease in insulin-like growth factor binding protein 3 (IGFBP-3). Administration of Hibiscus sabdariffa Linn., a powerful antioxidant, is expected to boost endogenous antioxidants, and thus prevents overtraining. The aim of this study is to determine the effect of H. sabdariffa on IGFBP-3 levels in rats under